Change in rate of orthodontic tooth movement and interleukin-1 beta level in gingival crevicular fluid in response to mechanical vibratory stimulation from electrical toothbrush - Sumit Suamphan (Prince of Songkla University Faculty of Dentistry (Oral Health Sciences), 2013)
Thesis (M.Sc., Oral Health Science)--Prince of Songkla University, 2010